Impact of Influenza on all-cause mortality in Portugal - Rodrigues, Ana Paula (2020)
Mortality during influenza epidemics depends: Influenza type and subtype; Incidence; Age groups affected; Characteristics of the population (ageing, chronic health conditions, social conditions).